"He died as he lived": Biopolitical Mediatization in the Death of David Goodall - Han, Samuel (Religions, 2019)
This article explores the nexus of biopolitics, mediatization and secularization, drawing out their relationship as it pertains to matters of assisted dying and euthanasia. In particular, it examines the dynamics of the media coverage of a highly-publicized case of euthanasia, namely, that of scientist David Goodall, based in Perth, Australia, who flew to Switzerland in May 2018 to end his own life at the age of 104. Focusing on the Australian Broadcasting Corporation's coverage, the article keys in on the theme of embodiment, discussing it within recent developments in social theory on the "secular body" and pain, suggesting that the mediatization of his death facilitated and structured an "environment" for staging and negotiating issues of biopolitical import. It then contextualizes this analysis within broader discussions on biopolitics and secularity.